Cranioplasty the use synthetic (Acrylic) or Autograft. - AL – Shalchy, Ali K. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Patients who undergo craniectomy or removal of part of the skull bone following trauma to give a release to the brain are later managed by auto graft, or synthetic acrylic graft.Patients and method: 20 patients transferred to specialized surgical hospital from U.S mellitary Ibn Sinna hospital with removal the skull bone implanted in the abdomenol wall or thigh and managed by returning of the bone to the scalp compared with 20 patients managed in our hospital to start by craniectomy and implantation of a synthetic bone graft acrylic, the comparism included the surgery, time of delay, out come, complication.Results: We divided the patients to group A and B, A were the ones treated by Autograft & B by synthetic graft (Acrylic). In both groups half of the patients were between 20 and 40 years of age, with male predominance, the delay of surgery were more group B, but the complications were more in group A, & 25% required surgical intervention & removal of the graft.Conclusion: we think that Acrylic cranioplasty is better than Auto graft cranioplasty in traumatic cases as it carries better cosmetic results & final out come.